Factorial! / Norul Fadhilah Ismail and Mahfuzah Mahayadin - Ismail, Norul Fadhilah; Mahayadin, Mahfuzah (Universiti Teknologi MARA, Negeri Sembilan, 2023)
Factorial is a mathematical operation that computes the product of al1l positive integers from 1 to a given non-negative integer. It is represented by the symbol “!”. The factorial of a non-negative integer n, denoted by n!, is the product of all positive integers that is less than or equal to n. Factorials are used to find the number of ways objects can be arranged, known as permutation and combination. It is a permutation when the order of each element matters such as the password of a lockbox, but it is a combination when the order does not matter, such as forming a soccer team from many players.